Merger and acquisition : effect of CEO retention on takeover premium - Wang, Chen Chung (2010)
This paper studies how different variables affect deal premiums in merger and acquisition deals, placing particular focus on the effect of the retention of target firm CEOs on the deal premiums, as measured by the Schwert Premium. We first focus on the general effect of retention on premiums, then drill in on retention effects in different situations, holding other variables constant. Our results show a significant negative loading on the variable interacting retention and target firm volatility when the Schwert Permium is regressed against it, providing significant evidence that acquirers pay less for riskier targets when they have to retain their CEOs in the new entity.